2022
DOI: 10.3390/sports10110184
|View full text |Cite
|
Sign up to set email alerts
|

The Neuromuscular Fatigue-Induced Loss of Muscle Force Control

Abstract: Neuromuscular fatigue is characterised not only by a reduction in the capacity to generate maximal muscle force, but also in the ability to control submaximal muscle forces, i.e., to generate task-relevant and precise levels of force. This decreased ability to control force is quantified according to a greater magnitude and lower complexity (temporal structure) of force fluctuations, which are indicative of decreased force steadiness and adaptability, respectively. The “loss of force control” is affected by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 112 publications
0
5
1
Order By: Relevance
“…Our findings were not in accordance with the evidence from previous research that has shown that usually, men were more fatigable than women when performing isometric contractions at low to moderate intensities [56][57][58][59] and that older subjects were less fatigable than young subjects for upper-and lower-limb muscles for an isometric-contraction fatiguing task at the same relative intensity [52,60]. However, it is well known that these discrepancies are task specific [57,61], rely on the details and demands of the task [17], and are associated with anatomical, biomechanical, and physiological factors [17,42,56,62,63].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings were not in accordance with the evidence from previous research that has shown that usually, men were more fatigable than women when performing isometric contractions at low to moderate intensities [56][57][58][59] and that older subjects were less fatigable than young subjects for upper-and lower-limb muscles for an isometric-contraction fatiguing task at the same relative intensity [52,60]. However, it is well known that these discrepancies are task specific [57,61], rely on the details and demands of the task [17], and are associated with anatomical, biomechanical, and physiological factors [17,42,56,62,63].…”
Section: Discussioncontrasting
confidence: 99%
“…In these studies, a reduction in the glenohumeral flexion, [19,51], an increase in the shoulder horizontal-abduction joint angles [46], changes in the trunk range of motion [19,46,51], and a combination of individual variations in the scapular kinematics to maintain an elevated shoulder position were observed, but also a decrease in movement accuracy during the task execution [20,52], with higher variability in movement trajectories in different axes [46,51].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…During strength exercises, movement variations depend on how force is produced and controlled. Force control is the ability to generate accurate and task-relevant force levels and is an important performance factor [ 12 ]. During strength exercises, this control is characterized by complex motor fluctuations, which reflect how the different body systems (nervous, musculoskeletal, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Non-linear measures have been proposed as relevant tools to analyze movement variability in order to understand how individuals cope with task demands [ 12 ]. Specifically, non-linear tools, such as entropy measurements or detrend fluctuation analysis (DFA), have been implemented to describe motor variability during force production tasks [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%